2019
DOI: 10.1029/2018ja026051
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Electron Diffusion Region of Magnetotail Reconnection Seen by the MMS Spacecraft on 11 July 2017

Abstract: We present results from the reconstruction of the electron diffusion region of magnetotail reconnection observed by the Magnetospheric Multiscale (MMS) spacecraft on 11 July 2017. In the event, the conditions were suited for the reconstruction technique, developed by Sonnerup et al. (2016, https://doi.org/10.1002/2016JA022430), that produces magnetic field and electron streamline maps based on a two‐dimensional, time‐independent, inertialess form of electron magnetohydrodynamic equation, assuming an approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

7
1

Authors

Journals

citations
Cited by 24 publications
(68 citation statements)
references
References 56 publications
5
61
2
Order By: Relevance
“…The V e,l, O‐L reversal (250 ± 150 km/s in Figure 4b; marked by the vertical blue line) and the reversal in B l O‐L (Figure 4a; marked by the vertical black line) are separated by ~0.9 s, suggesting the displacement of the stagnant point from the X‐line along the l direction (Hasegawa et al, 2019; Hwang et al, 2019). Around the V e,l, O‐L reversal, the out‐of‐plane V e,m, O‐L (Figure 4b) increases and the parallel heated electron flux is enhanced (red arrow in Figure 4c); J·E′ is negative (Figure 4e), which represents a transfer of energy from the plasma to the fields and has been reported at the outer edge of the EDR (Hwang et al, 2017) or in association with waves (Swisdak et al, 2018; Figure 3k).…”
Section: Reconnection Occurring In/around the Flux Ropementioning
confidence: 99%
“…The V e,l, O‐L reversal (250 ± 150 km/s in Figure 4b; marked by the vertical blue line) and the reversal in B l O‐L (Figure 4a; marked by the vertical black line) are separated by ~0.9 s, suggesting the displacement of the stagnant point from the X‐line along the l direction (Hasegawa et al, 2019; Hwang et al, 2019). Around the V e,l, O‐L reversal, the out‐of‐plane V e,m, O‐L (Figure 4b) increases and the parallel heated electron flux is enhanced (red arrow in Figure 4c); J·E′ is negative (Figure 4e), which represents a transfer of energy from the plasma to the fields and has been reported at the outer edge of the EDR (Hwang et al, 2017) or in association with waves (Swisdak et al, 2018; Figure 3k).…”
Section: Reconnection Occurring In/around the Flux Ropementioning
confidence: 99%
“…The MMS mission has for the first time enabled sufficiently accurate measurements of the electric current density with the plasma instruments (e.g., , and that capability allowed for the development of a new method for the invariant axis orientation of steady, 2-D structures (Hasegawa et al 2019). The method can be used to estimate the orientation of the X line and flux rope axis from single-spacecraft measurements of the magnetic field and current density.…”
Section: D-based Coordinate System For a 2-d Structure Based On Currementioning
confidence: 99%
“…A negative-topositive change in B l follows at~2234:02.8 UT (the vertical dashed blue line, "c"). Figure 1b, adopted from Figure 6 of Hasegawa et al (2019), illustrates possible magnetic field geometries in the l-n plane shown by blue lines with electron streamlines as dashed red arrows. At~2234:03.3 UT (the vertical dashed green line, "d"), V e,l changes from negative to positive, representing tailward-to-earthward outflow jets.…”
Section: Overview Of the Eventmentioning
confidence: 99%
“…(b) A simplified sketch (adopted fromFigure 6ofHasegawa et al, 2019) illustrating possible magnetic field geometries in the l-n plane seen in blue lines with electron streamlines as dashed red arrows. (b) A simplified sketch (adopted fromFigure 6ofHasegawa et al, 2019) illustrating possible magnetic field geometries in the l-n plane seen in blue lines with electron streamlines as dashed red arrows.…”
mentioning
confidence: 99%